Kesesuaian Habitat Peneluran dengan Wisata dan Daya Dukung Kunjungan di Kawasan Pelestarian Penyu Pantai Batu Kumbang, Kabupaten Muko-Muko, Provinsi Bengkulu - Santri Purari putra; Zulhamsyah Imran; Sulistiono Sulistiono (Institut Pertanian Bogor, 2023)
The balance of ecological and economic utilization plays a real role in maintaining the stability of turtle nesting habitat on the coast. This study aims to calculate the suitability index and visitation carrying capacity (DDK) of sea turtle nesting habitat to maintain the sustainability of its population. The survey was conducted in December 2020 to January 2021 at Batu Kumbang Beach, Pulau Baru Village, Muko-Muko Regency. The analysis used was the Habitat Suitability Index (IKH), Tourism Conformity Index (IKW), and visitation carrying capacity (DDK). The Mukomuko Turtle Conservation Nature Lovers Community (KPAKPM) reported that this beach is still predominantly used as a nesting habitat for green turtles (Chelonia mydas), olive ridley sea turtles (Lepidochelys olivacea), hawksbill turtles (Eretmochelys imbricata), and leatherback turtles (Dermochelys coriacea) in 2018. At least 35 heads of various types landed and laid eggs here and further decreased in 2020 with only 17 heads. The IKH showed that about 84.06%, 75.36%, and 75.36% belonged to the highly appropriate category and were spread out at Stations 1, 2, and 3, respectively. The suitability of the coastal area is at a value of 2.0 ≤ IKW < 2.5, and is categorized as sustainable. The number of visitors allowed according to DDK is only 84 people per day. Batu Kumbang Beach needs to be managed in a balanced manner with a conservation approach and beach ecotourism to ensure the sustainability and sustainability of nesting habitats for various types of turtles. Keywords: beach conservation, ecosystem, turtle nesting habitat